Small-particle-size nano W-Re-Y2O3 alloy powder and preparation method thereof
Through sol-gel method and complexation reaction, the problem of uneven distribution of tungsten, rhenium and yttrium oxide powders is solved, and the uniform preparation of nano-W-Re-Y2O3 alloy powder is achieved, which improves the sintering activity and mechanical properties of the material and reduces production costs.
Patent Information
- Application Number
- CN202510045315.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-13
AI Technical Summary
In the prior art, tungsten, rhenium and yttrium oxide powders are unevenly distributed during mixing, resulting in rhenium being prone to degenerate during sintering, affecting material properties.
A small particle size nano W-Re-Y2O3 alloy powder was prepared by sol-gel method. The complexing reaction in the citric acid solution was used to achieve uniform mixing and dispersion of tungsten, rhenium and yttrium oxide, and then reduction was carried out under a hydrogen environment to prepare a uniformly distributed nano alloy powder.
The uniform mixing of tungsten, rhenium and yttrium oxide at the molecular level is achieved, ensuring the complete solid solution of rhenium and the uniform distribution of Y2O3 particles, improving the sintering activity and mechanical properties of the alloy, and reducing production costs.
Smart Images

Figure CN119794335A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder metallurgy, and in particular relates to a small-particle-size nano W-Re-Y2O3 alloy powder and a preparation method thereof. Background Art
[0002] Friction stir welding is a solid-state welding technology with the advantages of small welding deformation and high strength of welded joints. It is widely used in the welding of materials such as aluminum alloys, steel, and titanium alloys. Since the stirring head rotates at high speed during welding, it is easily worn, which greatly affects the quality of the welded joint and the service life of the stirring head. Therefore, the stirring head needs to have excellent wear resistance and high-temperature mechanical properties. Tungsten (W) is the best tool material for friction stir welding of steel and other high-temperature alloys due to its excellent mechanical and thermal properties such as high strength, high hardness, high melting point, good thermal conductivity and electrical conductivity. However, since tungsten is brittle at room temperature (the ductile-brittle transition temperature of pure tungsten is about 400℃), it will recrystallize at high temperature (the recrystallization temperature of pure tungsten is 1100-1300℃), which will cause the tungsten stirring head to be prone to brittle fracture in the initial stage of welding. During the welding process, the high temperature may cause the performance of the stirring head to deteriorate, which limits the application and service life of tungsten in the field of friction stir welding. Therefore, improving the toughness, high-temperature stability and wear resistance of tungsten materials is of great significance for engineering applications.
[0003] By adding rhenium to tungsten, a tungsten-rhenium solid solution alloy can be formed. The addition of rhenium will cause tungsten lattice distortion and increase the resistance to dislocation movement, which greatly improves the toughness and recrystallization temperature of tungsten alloy and improves low-temperature brittleness. In addition, the addition of rhenium can refine the grains, improve the hardness and high-temperature stability of the alloy, which can increase the wear resistance of tungsten alloy. However, rhenium is a very expensive rare metal, which will lead to a significant increase in costs during production, which greatly limits the application of tungsten-rhenium alloys. Yttrium oxide (Y2O3) particles have the characteristics of high melting point (melting point up to 2410℃) and stable physical properties. Studies have shown that adding a trace amount of second phase particles Y2O3 to tungsten-rhenium alloys can pin grain boundaries and refine grains during sintering, which will significantly improve the deformation resistance and recrystallization temperature of tungsten alloys. In addition, the addition of Y2O3 will promote the densification process of the alloy during sintering and increase the hardness of the alloy, which will also improve the wear resistance of the alloy. Therefore, using a small amount of Y2O3 particles to replace part of the rhenium element in the tungsten-rhenium alloy to prepare W-Re-Y2O3 alloy can not only improve the strength and wear resistance of the alloy, but also reduce the production cost, broadening the application prospects of tungsten-rhenium alloy.
[0004] The prior art discloses some methods for preparing tungsten-rhenium alloy powders. For example, patent number CN119140825A discloses a method for preparing a spherical tungsten-rhenium alloy powder with high rhenium and low oxygen. Tungsten powder and rhenium powder are first ball-milled in a certain proportion, and then spray-dried and plasma spheroidized to obtain a uniform spherical alloy powder with low oxygen content. Although the above technical solution has the advantages of short preparation process, high density and good sphericity, due to the large difference in the physical properties of tungsten and rhenium during ball milling, rhenium will be unevenly distributed in the alloy powder. In addition, the powder may be contaminated by the ball milling medium during the ball milling process, affecting the performance of the powder after sintering.
[0005] At present, the main method for preparing W-Re-Y2O3 alloy powder is to mechanically alloy tungsten powder, rhenium powder and yttrium oxide powder by high-energy ball milling. However, the main problem is that these three powders are difficult to mix evenly, and rhenium is easy to aggregate during sintering, which ultimately affects the performance of the material. Therefore, it is necessary to explore a method that can achieve complete solid solution of tungsten and rhenium and uniformly introduce Y2O3 particles through process exploration. Summary of the invention
[0006] The purpose of the present invention is to provide a small-particle nano W-Re-Y2O3 alloy powder and a preparation method thereof in order to solve the problem of uneven distribution of tungsten, rhenium and yttrium oxide powders when mixed.
[0007] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0008] As a first aspect of the present invention, a small-particle nano W-Re-Y2O3 alloy powder is provided, and the small-particle nano W-Re-Y2O3 alloy powder is prepared by a sol-gel method; wherein the small-particle nano W-Re-Y2O3 alloy powder, in terms of mass percentage, comprises 79-94wt.% W, 10-20wt.% Re and 1-5wt.% Y2O3.
[0009] As a further optimization scheme of the present invention, the average particle size of the small-particle nano W-Re-Y2O3 alloy powder is 12 to 17 nm.
[0010] As a second aspect of the present invention, a method for preparing a small-particle-size nano W-Re-Y2O3 alloy powder is also provided, comprising the following steps:
[0011] (1) first dissolving citric acid in deionized water to obtain a citric acid solution, then dissolving ammonium metatungstate, ammonium perrhenate and yttrium nitrate as raw materials in the citric acid solution, and then heating in a water bath and stirring until a colloid is formed;
[0012] (2) drying the colloid obtained in step (1) to obtain a precursor, and then calcining the precursor to obtain nano oxide powder;
[0013] (3) reducing the nano oxide powder obtained in step (2) in a hydrogen environment to obtain the nano W-Re-Y2O3 alloy powder with a small particle size.
[0014] As a further optimization scheme of the present invention, in the step (1), the molar ratio of ammonium metatungstate to citric acid is 1 to 2:30.
[0015] As a further optimization scheme of the present invention, in the step (1), the temperature of the water bath heating is 60-90° C., the stirring speed is 300-500 r / min, and the stirring time is 4-6 h.
[0016] As a further optimization scheme of the present invention, in the step (2), the colloid is dried in a drying oven at 100-140° C. for 6-12 hours.
[0017] As a further optimization scheme of the present invention, in the step (2), the calcination temperature of the precursor is 400-500° C., and the calcination time is 6-12 hours.
[0018] As a further optimization scheme of the present invention, in the step (3), the reduction temperature is 600-900° C., and the reduction time is 2-4 hours.
[0019] As the third aspect of the present invention, a nano W-Re-Y2O3 alloy block is provided, which is prepared by sintering any of the above-mentioned small-particle nano W-Re-Y2O3 alloy powders, and the density of the nano W-Re-Y2O3 alloy block is 98.9%.
[0020] As a further optimization scheme of the present invention, the sintering preparation step is specifically as follows: in a vacuum environment, the small-particle-size nano W-Re-Y2O3 alloy powder is densified and sintered at a sintering temperature of 1700°C, a sintering pressure of 30 MPa, and a sintering time of 2 hours.
[0021] The beneficial effects of the present invention are:
[0022] (1) The nano W-Re-Y2O3 alloy powder prepared by the sol-gel method of the present invention realizes the uniform mixing and dispersion of tungsten, rhenium and yttrium oxide at the molecular level, and by controlling the reaction conditions, the average particle size of the prepared powder can be refined to about 12nm at the lowest. Compared with the traditional mechanical mixing method, the sol-gel method can ensure the uniform distribution of all components in the whole powder, which helps to improve the sintering activity of the powder and facilitates sintering densification at a lower temperature (1700℃).
[0023] (2) When the nano W-Re-Y2O3 alloy powder is prepared by the sol-gel method of the present invention, citric acid is first added to the preparation system. The citric acid reacts with water molecules in advance to form citric acid molecules. The carboxyl groups in the citric acid molecules subsequently form stable complexes with the metal ions added later, which helps to control the uniform distribution of the metal ions. Subsequently, a more uniform sol and an alloy powder with a finer particle size will be obtained.
[0024] (3) The entire preparation process of the present invention is carried out at a relatively low temperature, which can significantly reduce the oxidation and impurity incorporation of the powder during the preparation process, thereby obtaining W-Re-Y2O3 powder with high purity and low oxygen content, which helps the powder maintain excellent mechanical properties during subsequent sintering.
[0025] (4) When the nano W-Re-Y2O3 alloy powder is prepared by the sol-gel method, dispersed Y2O3 particles can be generated in situ during the calcination process, which helps the Y2O3 particles to be evenly distributed in the alloy block after the powder is sintered. Y2O3, as a stable oxide, can effectively inhibit the oxidation of tungsten and rhenium at high temperatures. The prepared W-Re-Y2O3 has wide application potential in many fields such as stir friction welding, nuclear energy industry and high-temperature structural materials.
[0026] (5) The preparation method of the present invention is simple, has low production cost, and is easy to implement large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a TEM image and a particle size distribution diagram of the oxide powder prepared in step 2 of Example 1 of the present invention;
[0028] Figure 2 TEM image and particle size distribution diagram of the nano 79wt.% W-20wt.% Re-1wt.% Y2O3 alloy powder prepared in Example 1 of the present invention;
[0029] Figure 3 is the XRD diagram of the nano 79wt.% W-20wt.% Re-1wt.% Y2O3 alloy powder prepared in Example 1 of the present invention;
[0030] Figure 4 This is a surface SEM image of a 79wt.% W-20wt.% Re-1wt.% Y2O3 alloy block prepared in Example 2 of the present invention;
[0031] Figure 5 This is a TEM image of a 79wt.% W-20wt.% Re-1wt.% Y2O3 alloy block prepared in Example 2 of the present invention;
[0032] Figure 6is a TEM image and a particle size distribution diagram of the oxide powder prepared in step 2 of Example 3 of the present invention;
[0033] Figure 7 TEM image and particle size distribution diagram of nano 89wt.% W-10wt.% Re-1wt.% Y2O3 alloy powder prepared in Example 3 of the present invention;
[0034] Figure 8 is the XRD diagram of the nano 89wt.% W-10wt.% Re-1wt.% Y2O3 alloy powder prepared in Example 3 of the present invention;
[0035] Fig. 9 is a TEM image and a particle size distribution diagram of the oxide powder prepared in step 2 of Example 4 of the present invention;
[0036] Fig.10 TEM image and particle size distribution diagram of the nano 94wt.% W-5wt.% Re-1wt.% Y2O3 alloy powder prepared in Example 4 of the present invention;
[0037] Fig.11 This is the XRD diagram of the nano 94wt.% W-5wt.% Re-1wt.% Y2O3 alloy powder prepared in Example 4 of the present invention.
[0038] Fig.12 is a TEM image and a particle size distribution diagram of the oxide powder prepared in step 2 of Example 5 of the present invention;
[0039] Fig.13 TEM image and particle size distribution diagram of the nano 93wt.% W-5wt.% Re-2wt.% Y2O3 alloy powder prepared in Example 5 of the present invention;
[0040] Fig.14 This is the XRD diagram of the nano 93wt.% W-5wt.% Re-2wt.% Y2O3 alloy powder prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Technicians in this field can make some non-essential improvements and adjustments to the present invention based on the above application content.
[0042] Unless otherwise specified, the methods used in the present invention are conventional methods known to those skilled in the art. If no specific conditions are specified, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0043] Example 1
[0044] The preparation method of the small-particle-size nano 79wt.% W-20wt.% Re-1wt.% Y2O3 alloy powder disclosed in this embodiment specifically includes the following steps:
[0045] (1) Add 15 g of citric acid to deionized water and stir until the citric acid is completely dissolved. Then, add 10.59 g of ammonium metatungstate, 2.88 g of ammonium perrhenate, and 0.34 g of yttrium nitrate to the solution in sequence. During this period, place the solution in a 70°C water bath and stir it at a speed of 300 r / min for 5 hours until a colloid is formed.
[0046] (2) The colloid obtained in step (1) is dried at 130° C. for 6 h, and then the dried colloid is calcined at 500° C. for 6 h to obtain nano-sized oxide powder. All reactions in this step are carried out in air.
[0047] (3) The oxide powder obtained in step (2) is placed in a mortar and ground for 5 minutes. Then, the ground powder is placed in a tubular furnace and reduced in a hydrogen environment at a temperature of 900°C for 2 hours to obtain a nano 79wt.% W-20wt.% Re-1wt.% Y2O3 alloy powder.
[0048] The nano 79wt.% W-20wt.% Re-1wt.% Y2O3 powder prepared in Example 1 was characterized.
[0049] Figure 1 The TEM image and particle size distribution diagram of the oxide powder prepared in step (2) show that the oxide powder is evenly distributed, the particle size of the powder particles is between 30nm-110nm, and the average particle size is 55nm. The ultrafine particle size means that the oxide powder has a larger specific surface area, which will increase the subsequent reduction reaction rate and help the reduction reaction to proceed fully.
[0050] Figure 2 The TEM image and particle size distribution diagram of nano 79wt.% W-20wt.% Re-1wt.% Y2O3 powder show that the particle size of the reduced alloy powder is between 5nm-23nm, and the average particle size is 12nm.
[0051] Figure 3 This is the XRD diagram of nano 79wt.% W-20wt.% Re-1wt.% Y2O3 powder. The results show that the reduced powder is a single BCC tungsten phase, and no obvious rhenium and other impurity phases are detected, which indicates that the prepared powder has high purity and rhenium has been completely dissolved in tungsten.
[0052] Example 2
[0053] On the basis of Example 1, in order to prove that the nanometer 79wt.% W-20wt.% Re-1wt.% Y2O3 powder prepared in Example 1 is easy to achieve sintering densification at a lower temperature, this example uses a hot press furnace to sinter the nanometer 79wt.% W-20wt.% Re-1wt.% Y2O3 powder prepared in Example 1, and the specific steps are as follows:
[0054] Nano 79wt.% W-20wt.% Re-1wt.% Y2O3 powder was densified and sintered in a vacuum environment using a hot press furnace. The sintering temperature was 1700°C, the pressure was 30MPa, and the sintering time was 2h to obtain a 79wt.% W-20wt.% Re-1wt.% Y2O3 alloy block with a density of 98.9%.
[0055] Characterization of the alloy bulk. Figure 4 The surface SEM image of the alloy block shows that there are almost no holes on the surface of the alloy block, which means that the alloy block has a high degree of densification. Statistics on the grain size of the alloy block show that the average grain size is about 3.1μm.
[0056] Figure 5 This is the TEM image of the alloy block. It can be found that the Y2O3 particles are evenly distributed inside the grains, which has a good dispersion strengthening effect.
[0057] Example 3
[0058] The preparation method of the small-particle-size nano 89wt.% W-10wt.% Re-1wt.% Y2O3 alloy powder disclosed in this embodiment specifically comprises the following steps:
[0059] (1) Add 20g of citric acid to deionized water and stir until the citric acid is completely dissolved. Then, add 11.93g of ammonium metatungstate, 1.44g of ammonium perrhenate, and 0.34g of yttrium nitrate to the solution in sequence. During this period, place the solution in a water bath at 80°C and stir it at a speed of 400r / min for 4h until a colloid is formed.
[0060] (2) The colloid obtained in step (1) is dried at 140° C. for 12 h, and then the dried colloid is calcined at 475° C. for 10 h to obtain nano-sized oxide powder. All reactions in this step are carried out in air.
[0061] (3) The oxide powder obtained in step (2) is placed in a mortar and ground for 5 minutes. Then, the ground powder is placed in a tubular furnace and reduced in a hydrogen environment at a temperature of 800°C for 3 hours to prepare a nano 89wt.% W-10wt.% Re-1wt.% Y2O3 alloy powder.
[0062] The 89wt.% W-10wt.% Re-1wt.% Y2O3 alloy powder prepared in Example 3 was characterized.
[0063] Figure 6 The TEM image and particle size distribution diagram of the oxide powder obtained in step (2) show that the oxide powder is evenly distributed, the particle size of the powder particles is between 50nm-110nm, and the average particle size is 68nm. The ultrafine particle size means that the oxide powder has a larger specific surface area, which will increase the subsequent reduction reaction rate and help the reduction reaction to proceed fully.
[0064] Figure 7 From the TEM image and particle size distribution diagram of the 89wt.% W-10wt.% Re-1wt.% Y2O3 powder after reduction prepared in step (3), it can be found that the particle size of the reduced alloy powder is between 6nm-22nm, and the average particle size is 17nm.
[0065] Figure 8 This is the XRD diagram of the 89wt.% W-10wt.% Re-1wt.% Y2O3 powder after reduction prepared in step 3. The results show that the reduced powder is a single BCC tungsten phase, and no obvious rhenium and other impurity phases are detected, which indicates that the prepared powder is of high purity and rhenium has been completely dissolved in tungsten.
[0066] Example 4
[0067] This embodiment provides a method for preparing a small-particle-size nano 94wt.% W-5wt.% Re-1wt.% Y2O3 alloy powder, and the specific steps are as follows:
[0068] (1) Add 25g of citric acid to deionized water and stir until the citric acid is completely dissolved. Then, add 12.60g of ammonium metatungstate, 0.72g of ammonium perrhenate, and 0.34g of yttrium nitrate to the solution in sequence. During this period, place the solution in a 90°C water bath and stir it at a speed of 500r / min for 6h until a colloid is formed.
[0069] (2) The colloid obtained in step (1) is dried at 120° C. for 8 h, and then the dried colloid is calcined at 450° C. for 8 h to obtain nano-sized oxide powder. All reactions in this step are carried out in air.
[0070] (3) The oxide powder obtained in step (3) is placed in a mortar and ground for 5 minutes. Then, the ground powder is placed in a tubular furnace and reduced in a hydrogen environment at a temperature of 700°C for 4 hours to prepare a nano 94wt.% W-5wt.% Re-1wt.% Y2O3 alloy powder.
[0071] The 94wt.% W-5wt.% Re-1wt.% Y2O3 alloy powder prepared in Example 4 was characterized.
[0072] Fig. 9 The TEM image and particle size distribution diagram of the oxide powder prepared in step (2) show that the oxide powder is evenly distributed, the particle size of the powder particles is between 30nm and 130nm, and the average particle size is 65nm. The ultrafine particle size means that the oxide powder has a larger specific surface area, which will increase the subsequent reduction reaction rate and help the reduction reaction to proceed fully.
[0073] Fig.10 From the TEM image and particle size distribution diagram of nano 94wt.% W-5wt.% Re-1wt.% Y2O3 powder, it can be found that the particle size of the reduced alloy powder is between 6nm-18nm, and the average particle size is 13nm.
[0074] Fig.11 This is the XRD diagram of nano 94wt.% W-5wt.% Re-1wt.% Y2O3 powder. The results show that the powder after reduction is a single BCC tungsten phase, and no obvious rhenium and other impurity phases are detected, which indicates that the prepared powder has high purity and rhenium has been completely dissolved in tungsten.
[0075] Example 5
[0076] The small-particle-size nano-sized 93wt.% W-5wt.% Re-2wt.% Y2O3 alloy powder disclosed in this embodiment has the following specific steps for its preparation:
[0077] (1) Add 25g of citric acid to deionized water and stir until the citric acid is completely dissolved. Then, add 12.46g of ammonium metatungstate, 0.72g of ammonium perrhenate, and 0.68g of yttrium nitrate to the solution in sequence. During this period, place the solution in a 60°C water bath and stir it at a speed of 400r / min for 4 hours until a colloid is formed.
[0078] (2) The colloid obtained in step (1) is dried at 100° C. for 10 h, and then the dried colloid is calcined at 400° C. for 12 h to obtain nano-sized oxide powder. All reactions in this step are carried out in air.
[0079] (3) The oxide powder obtained in step (2) is placed in a mortar and ground for 5 minutes. The ground powder is then placed in a tubular furnace and reduced in a hydrogen environment at a temperature of 600°C for 4 hours to prepare a nano 93wt.% W-5wt.% Re-2wt.% Y2O3 alloy powder.
[0080] The 93wt.% W-5wt.% Re-2wt.% Y2O3 alloy powder prepared in Example 5 was characterized.
[0081] Fig.12 The TEM image and particle size distribution diagram of the oxide powder prepared in step 2 show that the oxide powder is evenly distributed, the particle size of the powder particles is between 30nm and 90nm, and the average particle size is 46nm. The ultrafine particle size means that the oxide powder has a larger specific surface area, which will increase the reduction reaction rate and help the reduction reaction proceed fully.
[0082] Fig.13 From the TEM image and particle size distribution diagram of nano 93wt.% W-5wt.% Re-2wt.% Y2O3 powder, it can be found that the particle size of the reduced alloy powder is between 6nm-18nm, and the average particle size is 14nm.
[0083] Fig.14 This is the XRD diagram of nano 93wt.% W-5wt.% Re-2wt.% Y2O3 powder. The results show that the reduced powder is a single BCC tungsten phase, and no obvious rhenium and other impurity phases are detected, which indicates that the prepared powder has high purity and rhenium has been completely dissolved in tungsten.
[0084] Comparative Example 1
[0085] According to the article "Wang Hui, Ding Chenshi, Xie Zhuoming, et al. Study on mechanical properties and thermal stability of W-ZrC / HfC-Re alloy prepared by spark plasma sintering [J]. Rare Metal Materials and Engineering, 2024, 53(05): 1321-1331", when W-ZrC / HfC-Re powder was prepared by ball milling, when the Re addition amount was 3%, Re and Re2W3C signals were detected in the powder, which shows that 3% Re cannot be completely dissolved into the tungsten matrix when using the ball milling method. In addition, carbon impurities are introduced during the ball milling process. As the Re content increases, the signal of Re(W) in the powder prepared by ball milling increases, which means that the solid solution effect of Re in the tungsten matrix is worse. In addition, the SEM morphology of the W-ZrC / HfC-Re powder after ball milling was also observed in the report of this document. The results showed that the alloy powder prepared by ball milling was composed of many fragmented fine particles (about 100nm in size) and more large particles (about 500nm in size).
[0086] The average particle size of the nano W-Re-Y2O3 alloy powder prepared by the sol-gel method in Example 1 and Examples 3-5 of the present invention is between 12nm and 17nm, and the powder particles are evenly distributed. According to structural analysis, rhenium is completely dissolved in the tungsten matrix without any segregation.
[0087] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A small-particle nano W-Re-Y2O3 alloy powder, characterized in that: The small-particle nano W-Re-Y2O3 alloy powder is prepared by a sol-gel method; wherein the small-particle nano W-Re-Y2O3 alloy powder, in terms of mass percentage, includes 79-94wt.% W, 10-20wt.% Re and 1-5wt.% Y2O3.
2. The small-particle-size nano W-Re-Y2O3 alloy powder according to claim 1, characterized in that: The average particle size of the small-particle nano W-Re-Y2O3 alloy powder is 12-17 nm.
3. A method for preparing a small-particle-size nano W-Re-Y2O3 alloy powder as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: (1) first dissolving citric acid in deionized water to obtain a citric acid solution, then dissolving ammonium metatungstate, ammonium perrhenate and yttrium nitrate as raw materials in the citric acid solution, and then heating in a water bath and stirring until a colloid is formed; (2) drying the colloid obtained in step (1) to obtain a precursor, and then calcining the precursor to obtain nano oxide powder; (3) reducing the nano oxide powder obtained in step (2) in a hydrogen environment to obtain the nano W-Re-Y2O3 alloy powder with a small particle size.
4. The method for preparing a small-particle-size nano W-Re-Y2O3 alloy powder according to claim 3, characterized in that: In the step (1), the molar ratio of ammonium metatungstate to citric acid is 1 to 2:
30.
5. The method for preparing a small-particle-size nano W-Re-Y2O3 alloy powder according to claim 3, characterized in that: In the step (1), the temperature of the water bath heating is 60-90° C., the stirring speed is 300-500 r / min, and the stirring time is 4-6 h.
6. The method for preparing a small-particle-size nano W-Re-Y2O3 alloy powder according to claim 3, characterized in that: In the step (2), the colloid is dried in a drying oven at 100 to 140° C. for 6 to 12 hours.
7. The method for preparing a small-particle-size nano W-Re-Y2O3 alloy powder according to claim 3, characterized in that: In the step (2), the calcination temperature of the precursor is 400-500° C., and the calcination time is 6-12 hours.
8. The method for preparing a small-particle-size nano W-Re-Y2O3 alloy powder according to claim 3, characterized in that: In the step (3), the reduction temperature is 600-900° C., and the reduction time is 2-4 hours.
9. A nano W-Re-Y2O3 alloy block, characterized in that: The nano W-Re-Y2O3 alloy powder with small particle size is prepared by sintering, and the density of the nano W-Re-Y2O3 alloy block is 98.9%.
10. The nano W-Re-Y2O3 alloy block according to claim 9, characterized in that: The sintering preparation steps are specifically as follows: in a vacuum environment, the small-particle-size nano W-Re-Y2O3 alloy powder is densified by sintering at a sintering temperature of 1700° C., a sintering pressure of 30 MPa, and a sintering time of 2 hours.
Citation Information
Patent Citations
Alloy powder and preparation method thereof
CN106956009A
Submicron-structured top-layer scandium-containing cathode and preparation method
CN109390195A
Tungsten-rhenium alloy stirring head material for friction stir welding and preparation method of tungsten-rhenium alloy stirring head material
CN115647379A
Preparation method of high-dispersion nano tungsten / rhenium / lanthanum oxide composite powder
CN117532006A
Preparation method of tungsten-rhenium-tantalum pre-alloy powder
CN117773137A
Cited By
Preparation method of W-Re alloy with grain boundary irradiation damage relieving characteristic
CN122147117A